EMERGENCY LAPAROSCOPIC CHOLECYSTECTOMY: IS DEDICATED HOT GALL BLADDER LIST COST EFFECTIVE? - Khan, Saad Ullah; Soh, Jun Yi; Muhibullah, Nazli; Peleki, Aikaterini; Abdullah, Muhammad; Waterland, Peter William (Journal of Ayub Medical College Abbottabad, 2019)
Background: Acute presentation of gall stone disease is a common emergency. Resource limitation often results in unnecessary long waiting times and repeat hospital admissions. The aim of this study was to investigate if funding a dedicated hot gall bladder list is justified. Methods: Patients with acute gall stone related complications between 1st January 2016 and 31st December 2017 were studied. Outcome measures included the number of acute admissions, length of hospital stay (LOS), approximate cost per patient. The length of stay was identified as a critical outcome measure. Results: Fourteen hundred and ninety-five (11%) out of 14189 acute surgical admissions were related to gall stone complications. These included acute cholecystitis 576 (39%), biliary colic 485 (32%), pancreatitis 405 (27%) and jaundice 34 (2%). Twelve hundred and twenty-two patients accounted for 1461 admissions. 182 (15%) patients had recurrent admissions (35%) and on average stayed 11.2 days in the hospital compared to 5.8 days for that of single presentation. The cost of emergency LC (£2053) was less than half of elective LC following single emergency admission (£5661) and less than one third of Elective LC following recurrent admissions (£7453). A trust can save £1,891,784 per year by achieving 80% target. The savings can be used to fund a dedicated hot gall bladder list, releasing hospital beds and additional benefit of reducing the workforce days lost to sickness in general. Conclusion: Emergency LC is cost effective and savings made for such a service is sufficient to fund a dedicated hot gall bladder list. Keywords: Laparoscopic; Cholecystectomy; Laparoscopic cholecystectomy; Cost-Benefit Analysis; Hospital Costs; Cost Savings; Costs and Cost Analysis